Specifying Quality of Governance in Transition Economies with Cluster Analysis - UNLUKAPLAN, Ilter; CANIKALP, Ebru (Journal of Social Economics Research, 2017)
With the collapse of Soviet Russia, transition of communist countries towards the market economy not only caused an economic transformation but also formal and informal constraints, institutional structures and legal norms in society were changed. IMF’s and World Bank’s reports and governance concept containing neoliberal policies that took place in World Bank’s publications were important factors behind this transition. In this study, it is aimed to analyze quality of governance in transition economies by the year 2014. With this framework, Cluster analysis is performed by Ward (1963) Minimum Variance Method by using World Bank Governance and Freedom House dataset.